Corruption, Centralization and Competition: Evidence from Russian Public Procurement. Issue 5 (26th April 2018) - Detkova, Polina; Podkolzina, Elena; Tkachenko, Andrey
ABSTRACT: This paper estimates the impact of corruption on the incentives of procurers to maintain honest competition in tenders. Customers, who procure for themselves, and Agencies, who procure for the customers in their region are considered. Basing on a large dataset of open auctions conducted by Russian regional-level authorities in 2011, the analysis shows that in highly corrupt regions, Agencies fail to arrange competitive tenders and most of auctions have one bidder. Customers attract more bidders for large contracts, but rebates are usually low. Therefore, procurement centralization may reduce the corruption of Customers, but cannot solve the problem of low competition.